Advancement and challenges in MOSFET scaling. (1st November 2021) - Ratnesh, R.K.; Goel, A.; Kaushik, G.; Garg, H.; Chandan,; Singh, M.; Prasad, B.
Abstract: In this study, we enlighten about the field effect transistors (FET) and their technologies. As far as very large integration is concerned, researchers are continuously focusing on scaling the transistors in a way to improve the transistors efficiency. In today's era, electronics and semiconductor industries are developing in such a manner that different nano scaled transistors work with low power as well as low cost designs. However, scaling of metal oxide semiconductor field effect transistor (MOSFET) into nanometer scale induces some effects like short channel effects, tunneling effects, and threshold voltage effects etc., which degrade the performance as well as cause challenges to the fabrication process. This review article deals not only with the limitations of scaling and ways to resolve them but also contains detailed study of silicon nanowire and other distinctive nano FET. Moreover, these research finding are helpful in directing the current advancements in MOSFET technology and gave a brief sketch of possible future technologies. Graphical abstract: Image 1